Artikel Class X 2 Students' Response to Teacher's Directive Speech in the Learning Process at Sma Negeri 1 Sukosari - Kurniawan, Yudi (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
The aim of the research is to describe students' responses to directive speech acts in teacher and student interactions in class X 2 Indonesian language learning at SMA Negeri 1 Sukosari. This research uses a qualitative approach with descriptive research type. The research data is in the form of speech between teachers and students. Data collection techniques use interview, recording and note-taking techniques. Data analysis in research, namely data analysis and discussion, as well as conclusions. The research results showed that positive and negative student responses were in accordance with directive speech acts. According to the data collected, there are directive speech acts of asking, asking, commanding, prohibiting, forgiving, and encouraging.